Giant pericallosal artery aneurysm: case report and review of the literature - (:unkn) unknown (WALTER DE GRUYTER & CO, 2001)
Pericallosal artery aneurysms comprise 5% of all intracranial saccular aneurysms and are usually small. Giant cerebral aneurysms mostly occur in major arteries. To date, 12 cases of giant pericallosal artery aneurysm have been reported in the literature. An unusual giant thrombosed pericallosal artery aneurysm is reported here. A 65-year-old female presented with headache and personality changes. Computed tomography, magnetic resonance imaging, and cerebral angiography revealed a right-sided giant thrombosed pericallosal artery aneurysm. The patient was operated via an anterior interhemispheric approach and the neck of the aneurysm was successfully clipped. The postoperative period was uneventful. This rare lesion is one of few cases presented in the literature in which neuroradiologic and neuropathologic evaluation was completely performed and the neck of the aneurysm was clipped.
Keywords: giant aneurysm; pericallosal artery; thrombosed; ANTERIOR CEREBRAL-ARTERY; INTRACRANIAL ANEURYSMS; SACCULAR ANEURYSMS